Crack path dependence on inhomogeneities of material microstructure - Roberto Brighenti; Andrea Carpinteri; Andrea Spagnoli; Daniela Scorza (Fracture and Structural Integrity)
Crack trajectories under different loading conditions and material microstructural features play animportant role when the conditions of crack initiation and crack growth under fatigue loading have to beevaluated. Unavoidable inhomogeneities in the material microstructure tend to affect the crack propagationpattern, especially in the short crack regime. Several crack extension criteria have been proposed in the pastdecades to describe crack paths under mixed mode loading conditions. In the present paper, both the Sihcriterion (maximum principal stress criterion) and the R-criterion (minimum extension of the core plastic zone)are adopted in order to predict the crack path at the microscopic scale level by taking into account microstressfluctuations due to material inhomogeneities. Even in the simple case of an elastic behaviour under uniaxialremote stress, microstress field is multiaxial and highly non-uniform. It is herein shown a strong dependence ofthe crack path on the material microstructure in the short crack regime, while the microstructure of the materialdoes not influence the crack trajectory for relatively long cracks.